Pengaruh Variasi Kadar Lumpur pada Agregat Halus dan Penambahan Aditif terhadap Kuat Tekan Beton - Radiman Radiman; Hafiz Hamdani; Adryan Fitrayudha (Jurnal Talenta Sipil, 2026)
The acceleration of infrastructure development in Indonesia has increased the demand for concrete, yet the use of natural sand is often hindered by silt content exceeding the 5% standard limit. Excessive silt content inhibits the hydration process and significantly reduces concrete compressive strength. This study aims to analyze the effect of silt content variations in fine aggregates and the effectiveness of plasticizer additives on the compressive strength of concrete with a design strength of f'c = 20 MPa. The experimental research used silt content variations of 2.82%, 13.52%, 21.71%, and 30.81%. Testing included material analysis, slump tests, and compressive strength tests on 15x30 cm cylindrical specimens at 3 days, converted to 28-day estimates based on PBI 1971. The results indicated that increasing silt content caused a drastic decrease in slump values and compressive strength. At the highest silt content (30.81%) without additives, compressive strength decreased by 36.34% to only 12.73 MPa. However, adding Additon H.E at a dosage of 200 ml/sack consistently improved workability and restored concrete strength, with increases ranging from 26.47% to 35.83% compared to concrete without additives. In conclusion, plasticizer additives are proven effective as an engineering solution to optimize concrete performance even when using low-quality materials.